Conflicts in abstract argumentation systems - Martínez, Diego C. (2001)
In this work we explore the inclusion of the notion of multiple argument conflicts, those in which two or more arguments are involved. In formal systems of defeasible argumentation, arguments for and against a proposition are produced and evaluated to verify the acceptability of that proposition. The development of argumentation systems has grown in the last years [AG95, BV, Dung93, PRAK, Sim92, GS99] but no consensus has been reached yet on some issues, such as the representation of arguments, the way they interact, and the output of that interaction. Even then, the main idea in these systems is that any proposition will be accepted as true if there exists an argument that supports it, and this argument is acceptable according to an analysis between it and its counterarguments. Therefore, in the set of arguments of the system, some of them will be acceptable or justified arguments, while others not. Almost every system of this kind is based on the notion of binary conflicts between arguments. We consider here the existence of a more complex form of conflict, how to solve it, and the corresponding acceptability semantic.